Taryamāt Ma'āni al-Qur'ān al-Karīm wa taṭwiruhā - Saat Abdul Wahid (Al-Jami'ah: Journal of Islamic Studies, 2000)
The purpose of the revelation of the Qur'an is to make it the main source of Islamic law, way of life for individuals and society as well as to guide them in gaining the bliss of the world and hereafter. Most Muslims do not understand Arabic language, although the Qur'an was revealed in Arabic language. Therefore, most Muslims need translation of the Qur'an to understand it. Many western scholars who had a great study on Islam had tried to translate the Qur'an into European languages, whereas in fact they envied Islam and tried to put hatred in their translation. As a result, the Qur'an has been translated into many European languages. Because of this, many Muslim scholars try to translate the Qur'an in order to help other Muslims understand the Qur'an on one hand while on the other hand they try to prevent Islam from the spread of lies done by orientalist through their translation. The first Muslim who translated the Qur'an into English language was a British Muslim Muhammad Marmaduke Pickthall. In addition, the first Indonesia Muslim who translated Qur'an was Abdurrauf Fansuri from Singkel, Aceh, in the seventeenth century. The translation was then followed by other translations in Indonesian language.[Tujuan diturunkannya Al-Qur'an ialah menjadikan Al-Qur'an sebagai sumber utama bagi syariat Islam, tuntunan hidup bagi individu dan masyarakat, serta membimbing mereka unfuk mencapai kebahagiaan di dunia dan akhirat. Sebagaimana diketahui bahwa sebagian besar kaum muslimin di dunia tidak memahami bahasa Arab, padahal Al-Qur'an di- turunkan dalam bahasa Arab. Unfuk itu mereka memerlukan pertolongan dari terjemah Al-Qur'an untuk memahaminya.  Orang-orang orientalis telah berusaha menerjemahkan Al-Qur'an ke bahasa Eropa, padahal mereka sangat dengkikepadalslamdanberusaha memasukkan kebatilan-kebatilan dalam menerjemahkan Al-Qur'an. Mereka telah berhasil menerjemahkan Al-Qur'an ke berbagai bahasa Eropa hingga ratusan terjemahan. Maka para ulama Islam pun tidaklah diam, mereka berusaha menerjemahkan Al-Qur'an untuk mencegah tersebarnya kebatilan yang disebarkan oleh orang-orang orientalis melalui terjemahnya. Orang muslim yang pertama kali menerjemahkan Al-Qur'an al-karim kedalam bahasa Inggris adalah M. Marmaduke Pickthall, dia adalah orang Inggris asli. Adapun orang Muslim Indonesia yang pertama kali menerjemahkan Al-Qur'an al-Karim adalah Abdurrauf Fansuri, dari Singkel, Aceh pada abad tujuh belas, yang kemudian di susul oleh belasan terjemahan yang lain.]